2018
DOI: 10.1017/s095026881800081x
|View full text |Cite
|
Sign up to set email alerts
|

Waterborne Norovirus outbreak at a seaside resort likely originating from municipal water distribution system failure

Abstract: In May 2016 a Norovirus (NoV) gastroenteritis outbreak involved a high school class visiting a seaside resort near Taormina (Mascali, Sicily). Twenty-four students and a teacher were affected and 17 of them showed symptoms on the second day of the journey, while the others got ill within the following 2 days. Symptoms included vomiting, diarrhoea and fever, and 12 students required hospitalisation. Stool samples tested positive for NoV genome by Real-Time polymerase chain reaction assay in all 25 symptomatic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 36 publications
0
15
0
1
Order By: Relevance
“…After investigation, the research team indicated that damaged pipeline and inefficient water purification system for bacteria and virus were two primary reasons (Park et al, 2018). Another outbreak of norovirus gastroenteritis in Italy was associated with improper drinking water system caused by an old chlorination device and close proximity to suspected illegal sewage dumping (Giammanco et al, 2018). In another recent study conducted by McClung et al (2018), outbreaks associated with environmental as well as undetermined exposures to water were studied.…”
Section: Occurrence Of Waterborne Pathogensmentioning
confidence: 99%
“…After investigation, the research team indicated that damaged pipeline and inefficient water purification system for bacteria and virus were two primary reasons (Park et al, 2018). Another outbreak of norovirus gastroenteritis in Italy was associated with improper drinking water system caused by an old chlorination device and close proximity to suspected illegal sewage dumping (Giammanco et al, 2018). In another recent study conducted by McClung et al (2018), outbreaks associated with environmental as well as undetermined exposures to water were studied.…”
Section: Occurrence Of Waterborne Pathogensmentioning
confidence: 99%
“…Detection of enteric viruses in waters and contamination of aquatic environments have been reported by several studies worldwide (La Rosa et al, 2010a, b;Kamel et al, 2011;Prado et al, 2012;La Rosa et al, 2015;Osuolale & Okoh, 2015). In Sicily an outbreak of gastroenteritis occurred in Agrigento during March 2011, and NoV was identified in water samples from the public water system (Giammanco et al, 2014); a NoV gastroenteritis outbreak at a seaside resort near Taormina (Mascali, Sicily) originated from municipal water distribution system in May 2016 (Giammanco et al, 2018).…”
Section: Discussionmentioning
confidence: 91%
“…A total of 72 fresh and frozen shellfish and 16 environmental waters, were collected between 2012 and 2016. All the samples were screened for HAV, 439 Water samples included brackish water from the mussel farming centre in Syracuse); pipe water from Santo Stefano di Quisquina, Agrigento, where a Norovirus outbreak had occurred in 2011 (Giammanco et al, 2014) and from the province of Catania where in May 2016 a NoV outbreak had occurred (Giammanco et al, 2018); water from a desalter and seawaters (water from Lampedusa island, Agrigento, where a HAV outbreak had occurred in 2014); torrent water from the province of Caltanissetta.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Waterborne outbreaks caused by norovirus have been reported and associated with drinking tap water (Giammanco et al . ), contaminated water well (Qin et al . ) and wastewater intrusion into the water distribution network (Moreira and Bondelind ).…”
Section: Introductionmentioning
confidence: 99%